Normoglycemia alone is insufficient to prevent long term complications of hepatocellular adenoma in glycogen storage disease type Ib mice - Yiu, Wai Han (2009)
BACKGROUND/AIMS: Glycogen storage disease type Ib (GSD-Ib) patients deficient in a glucose-6-phosphate transporter (G6PT) manifest disturbed glucose homeostasis, myeloid dysfunctions, and hepatocellular adenoma (HCA). This study was conducted to evaluate whether maintaining normoglycemia in GSD-Ib could prevent HCA. METHODS: We infused neonatal GSD-Ib mice with adeno-associated virus (AAV) carrying G6PT and examined their metabolic and myeloid phenotypes for the 72-week study. RESULTS: The AAV vector delivered the G6PT transgene to the liver and bone marrow. Long-term metabolic correction was achieved alongside a transient myeloid correction. Hepatic G6PT activity was 50% of wild-type levels at 2 weeks post-infusion but declined rapidly thereafter to reach 3% of wild-type levels by age 6 to 72 weeks. Despite this, the infused mice maintained normoglycemia throughout the study, exhibited near normal growth and normalized serum metabolite profiles. However, all five AAV-treated GSD-Ib mice that lived over 50 weeks accumulated excessive hepatic glycogen and fat. Two mice developed steatohepatitis and multiple HCAs with one undergoing malignant transformation. CONCLUSION: Normoglycemia alone cannot prevent hepatic steatosis and glycogen accumulation or the development of HCAs in GSD-Ib, providing one explanation why GSD-Ib patients maintaining normoglycemia under intense dietary therapy continue at risk for this long-term complication.